Globally Rare BRCA2 Variants With Founder Haplotypes in the South African Population: Implications for Point-of-Care Testing Based on a Single-Institution BRCA1/2 Next-Generation Sequencing Study - Oosthuizen, Jaco; Kotze, Maritha J.; Van Der Merwe, Nicole; Myburgh, Ettienne J.; Bester, Phillip; van der Merwe, Nerina C. (Frontiers in Oncology, 2021)
Breast cancer patients historically benefitted from population-based genetic research performed in South Africa, which led to the development of founder-based BRCA1/2 diagnostic tests. With the advent of next-generation sequencing (NGS) technologies, the clinical utility of limited, targeted genetic assays were questioned. The study focused on mining NGS data obtained from an extensive single-institution NGS series (n=763). The aims were to determine (i) the prevalence of the most recurrent/founder variants in patients referred for NGS directly; and (ii) to explore the data for inferred haplotypes associated with previous and potential new recurrent/founder variants. The identification of additional founder variants was essential for promoting and potentially advancing to rapid founder-based BRCA1/2 point-of-care (POC) technology as a time- and cost-effective alternative. NGS revealed actionable BRCA1/2 variants in 11.1% of patients tested (BRCA1 – 4.7%; BRCA2 – 6.4%), of which 22.4% represented variants currently screened for using first-tier targeted genetic testing. A retrospective investigation into the overall mutation-positive rate for an extended cohort (n=1906), which included first-tier test results, revealed that targeted genetic testing identified 74% of all pathogenic variants. This percentage justified the use of targeted genetic testing as a first-tier assay. Inferred haplotype analysis confirmed the founder status of BRCA2 c.5771_5774del (rs80359535) and c.7934del (rs80359688) and revealed an additional African founder variant (BRCA2 c.582G>A – rs80358810). A risk-benefit analysis using a questionnaire-based survey was performed in parallel to determine genetic professionals' views regarding POC testing. This was done to bridge the clinical implementation gap between haplotype analysis and POC testing as a first-tier screen during risk stratification of breast and ovarian cancer patients. The results reflected high acceptance (94%) of BRCA1/2 POC testing when accompanied by genetic counselling. Establishing the founder status for several recurrent BRCA2 variants across ethnic groups supports unselected use of the BRCA POC assay in all SA breast/ovarian cancer patients by recent local and international public health recommendations. Incorporating POC genotyping into the planned NGS screening algorithm of the Department of Health will ensure optimal use of the country's recourses to adhere to the set standards for optimal care and management for all breast cancer patients.